2001
DOI: 10.1097/00001665-200111000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of Fibroblast Growth Factor Receptor 2 (FGFR2) in Japanese Patients with Craniosynostosis

Abstract: Recently, mutations of the fibroblast growth factor receptor ( FGFR ) genes have been detected in syndromic craniosynostosis. We examined nucleotide sequences of FGFR2 in Japanese craniosynostosis patients (Crouzon syndrome: 9 cases; Apert syndrome: 6 cases; scaphocephaly: 3 cases as non-syndromic patients) by polymerase chain reaction (PCR) followed by direct sequencing methods. The results demonstrated FGFR2 heterozygous mutations at codons 252, 290 of exon 7, and at codon 342, 354 of exon 9 in Crouzon syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…20 To date no such mutations have been identified in midline craniosynostoses. 21,25 Conclusions This is the first genetic study of craniosynostosis in which data from a cohort of twin pairs are examined. Our data are compatible with a multifactorial casuality, supporting both an environmental and genetic origin.…”
Section: Evidence For Genetic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 To date no such mutations have been identified in midline craniosynostoses. 21,25 Conclusions This is the first genetic study of craniosynostosis in which data from a cohort of twin pairs are examined. Our data are compatible with a multifactorial casuality, supporting both an environmental and genetic origin.…”
Section: Evidence For Genetic Factorsmentioning
confidence: 99%
“…20 No FGFR mutations, however, are found in nonsyndromic midline craniosynostoses. 21,25 Other putative causes of synostosis are environmental, such as intrauterine or perinatal factors. Graham, et al, 6,7 have suggested that intrauterine head constraint might be a cause of sagittal synostosis.…”
mentioning
confidence: 99%
“…(ii) Average mutation levels are positively correlated with donor age, and mirror epidemiological observations of paternal age for Apert syndrome births. (iii) Surprisingly, levels of the 755CÏŸT transition (encoding Ser252Leu), which is usually clinically silent in the heterozygous state but occasionally causes Crouzon syndrome (26,27), are also elevated (but overall, are Ï·1.7-fold lower than 755CÏŸG) and also positively correlate with donor age. Levels of the third possible substitution, 755CÏŸA (encoding a stop codon) are not increased.…”
mentioning
confidence: 99%
“…However, it is rarer in Asian population: only several cases were reported in Japan (10, 11) and no reports as yet in Korea. Cohen (12) in 1993 classified this syndrome into 3 clinical subtypes and suggested that these subtypes might not be classified as separate entities, even though these classifications have important diagnostic and prognostic implications.…”
Section: Discussionmentioning
confidence: 99%